Couple honored at open house (Raton Range Raton, New Mexico, 1989)
Newspaper Article on the 60th Anniversary of Garland and Etta Arnold.
Master list item #: 87
File location is in the Raton File Cabinet
Keywords: Arnold, Garland; Arnold, Etta; Cooke, Homer F; Arnold, Orville; Arnold, Ruth; Arnold, Pearl; Arnold, Oda; Arnold, Marion; Arnold, Sharron; Arnold, Luetta; Arnold, Garland; Arnold, Willard; Cunico, Chris; Cunico, Karl; Burks, Tony; Burks, (Mrs.); Burks, Christy; Burks, Toni; Hronish, John; Arnold, Mike; Arnold, (Mrs.); Andersen, Marion; Andersen, Bill; Turner, Carrie; Turner, Rebecca; Lehman, Richard; Cannedy, Sally; Anderson, Bill; Weisler, Pete; Weisler, Sharron; Whatley, Dee; Whatley, Joe; Whatley, Quinton; Dupree, John; Dupree, Robin; Arnold, Garland; Arnold, Ryan; Arnold, Jason; Arnold, Willard; Arnold, (Mrs.); Arnold, Chad; Arnold, Cassie; Daniels, Barbara; Curran, Velma; Ainsworth, Laurveil; Gish, PennySta; First Christian Church; Local History; Biography; Life and Customs; Marriage; Celebration; Anniversary; Raton, New Mexico; Broken Arrow, Oklahoma; Clayton, New Mexico; Estes Park, Colorado; Iowa Park, Texas; Fayetteville, Arkansas; Dupree, South Dakota